The Influence of The Marketing Mix on Buying Decision (Study on Rb Collection Pasar Baru Bekasi) - Netti Natarida Marpaung (International Journal of Education, Information Technology, and Others, 2022)
This study aims to determine and analyze the influence of the marketing mix in the store "RB Collection" Pasar Baru Bekasi. The research in this thesis uses quantitative methods. The variables that are connected in this study are the Marketing Mix variable (X), and the Purchase Decision variable (Y). The data sources used consisted of primary data, namely data obtained directly from research respondents through questionnaires, interviews, and observations. The population and sample in this study were RB Collection consumers in Pasar Baru Bekasi City. The test was carried out using SPSS 26. Based on the results of the partial test (t test) it can be concluded that the marketing mix variable has a significant influence on purchasing decisions because the value of tcount (11.852) > ttable (0.198) with a significance of 0.000 <0.05. The marketing mix variable has a dominant influence that is equal to 0.771. The coefficient of determination of the Adjusted R-Square value obtained is 0.594, indicating that about 59.4% of the Y variable (purchase decisions) can be explained by the marketing mix variable (X). Or practically it can be said that the contribution of the marketing mix to the purchasing decision variable is 59.4%.